A novel approach for critical bone defect repair - Schneiderhan, Adam, author; Prawel, David, advisor; Popat, Ketul, committee member; Séguin, Bernard, committee member (Colorado State University. Libraries, 2022)
Critical bone defects are defined as defects that will not naturally heal over a patient's lifetime, even with surgical stabilization. When these occur in the long bones of the axial skeleton (secondary to trauma, tumor resection, etc.), limb-sparing surgery can be performed to avoid amputation of the limb. This procedure typically involves the installation of a steel locking plate over the defect, along with an endoprosthesis or allograft to fill the void of resected bone. Much progress has been made in the natural bone regeneration using tissue engineering (TE) scaffolds in place of these grafts. Porous hydroxyapatite (HAP) is a well-established bone TE scaffold biomaterial but lacks sufficient mechanical strength when fabricated at porosities shown to best induce osteogenesis. To remedy this, polymers such as polycaprolactone (PCL) are often mixed with HAP to fabricate scaffolds with increase load-bearing capacity. However, the addition of PCL makes the scaffold less osteogenic and dramatically slows the degradation rate of the scaffold. This translates into reduced new bone volume where the PCL cannot be remodeled as new bone is formed. This project involves a pilot clinical trial of a novel method that augments the gold-standard limb-sparing procedure by implanting a 3D printed endoprosthetic "sleeve" device that attaches to the locking fixation plate and contains and protects the brittle HAp scaffold. The PCL sleeve alleviates the dependency on scaffold strength which enables use of the most osteogenic possible biomaterials at ideal porosities to maximize the rate and density of new bone formation. The purpose of the study is to clinically validate the construct design and surgical procedure. Thus far, pilot limb-sparing surgeries have been performed on 4 client-owned dogs, in which sleeve-scaffold devices were installed in the critical defects caused by the removal of osteosarcomas in distal epiphyseal radii. Recombinant human bone morphogenic protein-2 (rhBMP-2) was added to the scaffolds to further encourage osteogenesis. Mechanical tests were performed on both the sleeves alone and the full construct installed in canine cadaver limbs. Results from this testing demonstrate the sleeve's ability to prevent mechanical failure of the HAp scaffolds. Similarly, no scaffold failure has been observed in clinical trial patients, with some having the device installed for greater than 24 weeks. Additionally, pressureometry and gait analysis confirmed excellent return of limb function in these animals. However, to date, no new bone formation has been observed within the scaffold devices, which has likely been inhibited by anti-cancer treatment. Regardless, results from ex vivo testing and the clinical trial validate the construct design and the viability of our novel method for protecting and maintaining brittle bone tissue engineering scaffolds, while aiding in restoration of normal limb function.
Keywords: limb sparing; critical bone defects; tissue engineering